2015
DOI: 10.1002/chem.201500100
|View full text |Cite
|
Sign up to set email alerts
|

Towards Solar Energy Storage in the Photochromic Dihydroazulene–Vinylheptafulvene System

Abstract: One key challenge in the field of exploitation of solar energy is to store the energy and make it available on demand. One possibility is to use photochromic molecules that undergo light-induced isomerization to metastable isomers. Here we present efforts to develop solar thermal energy storage systems based on the dihydroazulene (DHA)/vinylheptafulvene (VHF) photo/thermoswitch. New DHA derivatives with one electron-withdrawing cyano group at position 1 and one or two phenyl substituents in the five-membered r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 29 publications
3
87
0
Order By: Relevance
“…In closing, we emphasize that the potential of using ESA as a photochemical design tool is heavily unexplored. Therefore, given the positive results reported in this minireview and the proven merits of computational modeling in studies of molecular photoswitches, it appears worthwhile for future research to investigate whether the ESA concept also can be employed to improve molecular photoswitches in other aspects than those discussed herein.…”
Section: Discussionmentioning
confidence: 99%
“…In closing, we emphasize that the potential of using ESA as a photochemical design tool is heavily unexplored. Therefore, given the positive results reported in this minireview and the proven merits of computational modeling in studies of molecular photoswitches, it appears worthwhile for future research to investigate whether the ESA concept also can be employed to improve molecular photoswitches in other aspects than those discussed herein.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to perform reliable TS calculations in the junction in order to ascertain whether the kinetics of ring closure also agrees with experiment. Nevertheless, we have previously observed that the larger the dha − vhf energy difference, the faster is the vhf -to- dha conversion272829.…”
Section: Resultsmentioning
confidence: 97%
“…The basic physical effect responsible for this surprising feature is the delocalized nature of the polaritonic states obtained under collective strong coupling, which require a treatment of the whole collection of molecules as a single polaritonic supermolecule. For the specific model studied here, this strategy could resolve one of the main problems of solar energy storage; that is, how to efficiently retrieve the stored energy from molecules that are designed for the opposite purpose, i.e., for storing energy very efficiently under normal conditions [20,21]. By reversibly bringing the system into strong coupling (e.g., through a moving mirror that brings the cavity into and out of resonance), one could thus trigger the release of the stored energy through absorption of a single ambient photon.…”
Section: Prl 119 136001 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…We thus investigate a class of reactions that release energy, i.e., where the initial starting state after absorption of a photon has higher energy than the final state, in which all involved molecules have undergone a reaction. We focus on a class of model molecules with a structure as proposed for use in solar energy storage [19][20][21], described within a simplified model treating a single reaction coordinate, as shown in Fig. 1(a).…”
mentioning
confidence: 99%